Exploring the Therapeutic Landscape: A Systematic Review on the Anti-inflammatory Effects of Probiotics in Colitis-associated Colorectal Cancer - Suswita, Rini; Alvarino; Eryati Darwin; Jamsari (Majalah Kedokteran Andalas, 2024)
Background: Colorectal cancer is closely linked to chronic inflammation; long-standing colitis confers a 2–3-fold higher risk. Modulating the gut–immune axis with probiotics may attenuate the inflammatory microenvironment of colitis-associated colorectal cancer (CAC). Objective:To evaluate the anti-inflammatory effects of probiotics in CAC animal models. Methods: We searched PubMed, ScienceDirect, and Wiley Online Library; 248 records were screened and 9 studies met inclusion. Risk of bias was appraised using SYRCLE RoB. Results: Probiotic treatment consistently reduced clinical severity, down-regulated inflammatory markers, and modulated key signaling pathways in CAC models. Nonetheless, evidence was heterogeneous, sample sizes were small, and dosing, strains, and formulations varied; safety reporting was limited. Conclusions: Probiotics show promise as anti-inflammatory adjuncts in CAC based on animal studies. Rigorous, standardized preclinical work and well-designed trials are needed to define optimal strains, dosing, and formulations, and to confirm efficacy and safety for translation.